School dropout in Latin America as a social conflict - Saturnino, Carrasco Moreno Angel (Technium Social Sciences Journal, 2021)
Education worldwide is a process in which man prepares himself for life in society, that is to say, it is a process of socialization, which requires a very diverse learning, since it is not only knowledge, but also techniques, guidelines and aptitudes, which recognize a person as part of society. The high number of students in Latin America who drop out of school without completing the educational stage is very significant, which originates onerous expenses in society. The strategies that have been used to prevent dropout are ineffective and weak, and instead of decreasing it has been progressively increasing, since these strategies have not been focused on the various causes that lead to dropout. It is perceived that dropout is a social manifestation caused by internal and external cases within the same community environment. Likewise, it is pointed out that school evasion is considered a social phenomenon in which people leave school temporarily or permanently to a teaching stage, which participates in formal learning (De Aguinaga &Barragán,2007, p. 2).